Analisis Faktor –Faktor Yang Mempengaruhi Pertumbuhan Laba Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Manufaktur Periode 2015 – 2019 - Maulina Agustin; Yuniorita Indah; Nurshadrina Kartika (STIE Mandala Jember, 2020)
The purpose of this research is to examine and analyze the effect of Profitability Ratios, Market Value Ratios, Leverage Ratios, and Activity Ratios on Profit Growth with Firm Size as Moderation Variable by using the Basic Sector and Chemical Manufacturing company objects listed on the Indonesia Stock Exchange. This research was conducted for five consecutive years, from 2015 to 2019 which included 11 sample companies, which were taken using purposive sampling technique. Data were analyzed using multiple regression analysis and residual test for moderating variables. The results showed that only the Market Value Ratio had a partial effect with a significant value of 0.013, while the Profitability Ratio, Leverage Ratio, and Activity Ratio had no significant effect on profit growth, while for the company size variable as a moderating variable only the activity ratio was significant and with the presence of variables. moderation can strengthen or weaken the relationship between the independent variable and the dependent variable.